2017
DOI: 10.1002/clc.22780
|View full text |Cite
|
Sign up to set email alerts
|

Relation of premature atrial complexes with stroke and death: Systematic review and meta‐analysis

Abstract: ). The funding sources had no involvement in the study design; in the collection, analysis, or interpretation of data; in the writing of the report; or in the decision to submit the article for publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
0
27
1
1
Order By: Relevance
“…The median number of APCs was 1.27 per hour; the number of APCs increased according to age, and the presence of APCs was the second strongest independent predictor of cardiovascular events, after age. Huang et al 15 conducted a meta-analysis of the association between APCs and cardiovascular events. Frequent APCs were associated with a 1.41-fold increased risk of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The median number of APCs was 1.27 per hour; the number of APCs increased according to age, and the presence of APCs was the second strongest independent predictor of cardiovascular events, after age. Huang et al 15 conducted a meta-analysis of the association between APCs and cardiovascular events. Frequent APCs were associated with a 1.41-fold increased risk of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we did not find a significant relationship between fPAC and stroke. In a meta‐analysis, Huang et al concluded that further research needed to clarify this relationship (Huang et al, ). In our study, there was no significant relationship between stroke and fPAC.…”
Section: Discussionmentioning
confidence: 99%
“…increased risk of all-cause mortality and stroke. 43 However, without the benefit of continuous arrhythmia monitoring in these studies, it cannot be determined if the premature atrial contractions were the cause of these poor outcomes or if they were simply a marker for undetected AF.…”
Section: Study Design-related Factorsmentioning
confidence: 97%